PERFORMANCE ASSESSMENT OF COOPERATIVE FINANCIAL INSTITUTIONS USING THE BALANCED SCORECARD CONCEPT - Subarkah, Johny (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to determine the effect of the performance of cooperative financial institutions by using the concept of a balanced scorecard. Balance scorecard attributes used as independent variables in this study are financial, customer, internal business, growth and learning perspectives. The cooperative financial institution that is the object of research is the Putri Manunggal Cooperative in Sukoharjo. This research is a type of quantitative descriptive research. The population in this study were the employees and customers of the Putri Manunggal Cooperative, while the sample used was selected through a random sampling technique by distributing questionnaires to 500 respondents. The technique of collecting data is a questionnaire, which is done by giving a set of questions or written statements to the respondents to be answered. The weight of the assessment or the number of the questionnaire results in this study is in accordance with what is described in the Likert scale. The dependent variable in this study is Cooperative Performance (Y), while the independent variables in this study are financial perspective (X1), customer perspective (X2), internal business process perspective (X3), and learning and growth perspective (X4). The data analysis technique of this research uses multiple linear regression analysis, F test, t test, and coefficient of determination (R2) test. The results showed that the financial, customer and internal business perspective variables partially had a significant effect on financial performance. While the growth and learning perspectives have no significant effect on financial performance. Simultaneously the financial, customer, internal business, growth and learning perspectives have a significant effect on financial performance. Keywords: balance scorecard, financial performance, cooperative financial institution